Pengaruh Tindakan Investasi Infrastruktur dan Pelayanan Terhadap Masyarakat Serta Kepemilikan Institusional Terhadap Profitabilitas - Dias Adi Dharma; Reny Andriyanty (Unversitas Prof. Dr. Moestopo (Beragama), 2022)
This research objective was to analyze the impact of infrastructure investment actions on the community and institutional ownership on the profitability of mining companies listed on the IDX from 2017 to 2019. The research method was descriptive quantitative with panel data regression analysis on 18 mining companies listed on the IDX data time. The series is data for the period 2017 to 2019. The results concluded that there was a significant relationship between infrastructure investment actions and services provided primarily for the public interest through trade and community services and institutional ownership variables on the profitability of mining companies analyzed in this study. The investment action variable had a negative effect so that it suppressed the company's profitability. The